Pengembangan Lembar Kerja Peserta Didik Berbasis Inkuiri Terbimbing untuk Meningkatkan Hasil Belajar Siswa pada Materi Koloid - Firayanti; Rahmanpiu; Rustam Musta (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
The research “Development of Guided Inkuiry-Based Student Worksheets to Improve Student Learning Outcomes on Colloidal Material” aims to determine the feasibility, practicality, and efeectivennes of guided inkuiry-based student worksheets on colloidal material. The research and development (R&D) the Thiagarajan model. The development procedure includes the defining, designing and developing stages. The sample in this study were 10 students of class XI IPA 4. The research instrument used validation sheets, test questions sheets and student response questionnaire sheets. The research data were then analyzed using descriptive analysis. The results showed that the guided inquiry-based worksheet products that had been developed and assessed by expert validators were in the average percentage  of 84,83%, student responses to guided inquiry-based worksheets obtained a percentage of 78,32% in the category feasible and the level of effectiveness obtained by moderate category cazb be said to be quite effective.